A survey on the practicality of rainwater harvesting in offices building at Klang Valley / Mohd Amarul Haikal Abd Latif - Abd Latif, Mohd Amarul Haikal (Faculty Architecture, Planninng and Surveying, 2014)
The objective of this research is to identify the advantage of rainwater harvesting technology. Other than that, this research also completed to identify the challenge relating to rainwater harvesting also to see whether this product is practical to get applied so as to reduced monthly spending. This research is completed to several of case study. The area of the research is around Klang Valley. The number of case study of this research is two (2) building which is applied this system in their building. The method o f carrying out this research is by questionnaire and interview. The target respondent may be the competent person which handle and caring for rainwater harvesting program. That is due to the fact to obtained this detail and accurate data in the person that were interviewed. The conversation from interview is going to be recorded and it's going to be transcribed. Only the top data will always be transcribed which associated with the research. Then, all the data is going to be analyzed to have the finding and to achieve the objectives of this research. When the information analysis completed, it indicate which the main function involving rainwater harvesting system is good for irrigation of landscaping and garden. Apart from that, the consequence of finding also shows that the rainwater harvesting system remains quite new because every one of case study building have apply this product below than 5 decades. Mostly the reasons why this system is applying within the building due to reduce monthly water payment cost. For your initial cost, the results with the finding indicate that it's quite expensive however the installation cost is depend kind of system that was used. If the system is simple and the effective use of the water is just for one objective, there is you don't need to installed additional portion of rainwater harvesting. For that main problem involving rainwater harvesting system that usually arise relating to rainwater harvesting is high initial price tag and faulty with pump. From this particular research, it may be conclude that this rainwater harvesting system is usually a practical approach and have potential to be used widely in Malaysia on account of climate and other factors that produce rainwater harvesting is required. It is has lot of benefits for the human being as well as environment.